2005
DOI: 10.1124/mol.105.012153
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Adenylate Cyclase and Receptor Internalization by Novel Dopamine D1 Receptor Agonists

Abstract: Structurally dissimilar dopamine D 1 receptor agonists were compared with dopamine in their ability to activate adenylate cyclase and to internalize hemagglutinin-tagged human D 1 receptors in a stably transfected human embryonic kidney cell line. Thirteen dopamine D 1 receptor agonists were selected rationally from three different structural classes: rigid fused ring compounds [dihydrexidine, dinapsoline, dinoxyline, apomorphine, and (5aR,11bS)-4,5,5a,6,7,11b-hexahydro-2-propyl-3-thia-5-azacyclopent-1-ena[c]-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 34 publications
8
58
0
Order By: Relevance
“…More recent evidence indicates, however, that certain antagonists can internalize certain receptors (Berry et al, 1996;Roettger et al, 1997), and that the internalization process can be agonist-specific depending on the cellular milieu specific to that receptor expression system (Ryman-Rasmussen et al, 2005). These observations complement the fundamentals of functional selectivity, which state that the intrinsic activity of a ligand Functional data represent the means7SEM (in nM) of three to five independent experiments.…”
Section: Aripiprazole Fails To Stimulate Internalization Of the Flag-supporting
confidence: 45%
See 1 more Smart Citation
“…More recent evidence indicates, however, that certain antagonists can internalize certain receptors (Berry et al, 1996;Roettger et al, 1997), and that the internalization process can be agonist-specific depending on the cellular milieu specific to that receptor expression system (Ryman-Rasmussen et al, 2005). These observations complement the fundamentals of functional selectivity, which state that the intrinsic activity of a ligand Functional data represent the means7SEM (in nM) of three to five independent experiments.…”
Section: Aripiprazole Fails To Stimulate Internalization Of the Flag-supporting
confidence: 45%
“…Our study indicates that neither aripiprazole nor the typical partial agonist (À)3PPP induce a significant degree of internalization relative to basal levels, indicating that either D 2 ligands with low intrinsic activity fail to produce D 2 receptor internalization or that these two compounds are unique in their promotion of receptor conformations that cannot be phosphorylated by the appropriate kinases. Although (À)3PPP can desensitize the D 2 receptor (Lahti et al, 1998), it is clear that this does not necessarily predict internalization (Lewis et al, 1998;Ryman-Rasmussen et al, 2005). Further experiments are needed to determine whether D 2 receptor internalization is a product unique to ligands that are full agonists, or if aripiprazole and (À)3PPP are unique in their inability to internalize the D 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In studies using D1-HEK cells, synthetic ligands were identified that induced cAMP production, but not receptor internalization, and others that were super agonists for internalization. 22 SK-N-MC cells endogenously express D1, but not D5 receptors, 21,26 and therefore represent a useful cell line to compare the pharmacology between endogenously expressed/coupled D1 receptors to D1-transfected cells. In contrast to the results with D1-HEKs, the native ligand and four synthetic agonists all induced a Gi/o impedance response in SK-N-MC cells.…”
Section: Discussionmentioning
confidence: 99%
“…This was also true in the adenylate cyclase assay using D1-HEK cells. 22 Both partial agonists had greater efficacy in U-2 cells than in SK-N-MC cells. The greater efficacy for a Gs-like response could reflect biased coupling by these ligands, but could also be due to cellular or assay differences that are not understood.…”
Section: Endogenous Receptor Signalingmentioning
confidence: 99%
See 1 more Smart Citation